2021
DOI: 10.3390/nu13061897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Intake on Cutaneous and Systemic Inflammation in Mice with Acute Experimental Psoriasis

Abstract: Background: Psoriasis is a systemic inflammatory disorder, primarily characterized by skin plaques. It is linked to co-morbidities including cardiovascular disease and metabolic syndrome. Several studies demonstrate that dietary habits can influence psoriasis development and severity. However, the effect of different dietary protein levels on psoriasis development and severity is poorly understood. In this study, we examine the influence of dietary protein on psoriasis-like skin disease in mice. Methods: We fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Although we had examined the same association between various protein intakes and IE, there were no significant associations. This is consistent with a previous study in mice with psoriasis-like conditions whereby the feeding of high-protein diets exacerbated systemic inflammatory responses but had little effect on cutaneous conditions ( Knopp et al., 2021 ). These results corroborated the idea that a frequent intake of high-protein foods in diets promoted the associated risks of AD by manifesting on top of the atopy predisposition.…”
Section: Discussionsupporting
confidence: 93%
“…Although we had examined the same association between various protein intakes and IE, there were no significant associations. This is consistent with a previous study in mice with psoriasis-like conditions whereby the feeding of high-protein diets exacerbated systemic inflammatory responses but had little effect on cutaneous conditions ( Knopp et al., 2021 ). These results corroborated the idea that a frequent intake of high-protein foods in diets promoted the associated risks of AD by manifesting on top of the atopy predisposition.…”
Section: Discussionsupporting
confidence: 93%
“…A dietary protein deficit was noted for patients who scored >15 points on the AUDIT test. Zacheim et al [ 66 ] and Knopp et al [ 67 ] indicated that the severity of psoriatic lesions is not dependent on dietary protein [ 31 , 42 , 43 ]. Unfortunately, there is a lack of long-term studies on protein intake versus inflammatory marker levels.…”
Section: Discussionmentioning
confidence: 99%